(untitled) (Anclajes, 2024)
We intend to analyze the representations of the "other" in Mário de Andrade´s Os contos of Belazarte (1934). We wonder who the "other" in these texts is, how the author discusses the "social other," how far he places himself from the nineteenth-century conceptions of the "other," to what extent he reformulates previous lineages, and what place he assigns to otherness in the attempt to establish a national identity. There are two problems to consider in our analysis: firstly, the tension between aesthetics and ideology, manifested in Mário de Andrade´s production of literary criticism in the 20s-30s decade turning point; secondly, the social commitment that the author thematizes in these stories, which also seems to be in tension with the sympathy for popular subjects and certain ideological position that responds to the precepts of a literate and exclusive elite.